RESILIÊNCIA: UM ESTUDO PARA A CAPTAÇÃO DA DIMENSÃO MAIS DINÂMICA E SUBJETIVA DOS FATORES DE PROTEÇÃO - Torres, Luis Fernando (2010)
Studying resilience is to ask whether the individual is able to handle adversity, overcome it and still become a better individual, the answer should be yes. But the answer in this context is subjective, because the answer will be based on the perception of the subject based on a response in terms of what is sure to respond before a question like this. That said, this study sought to find a group of professionals who were ahs been facing organizational changes and how they should signified this change, if it was perceived as positive or negative how could this phenomenon be appointed. Semi-structured interviews were conducted with the goal to better approach of resilience phenomenon, since the objective of the research was exploratory, and also few studies have been done in the field of resilience with a focus on positive psychology and, against this background this paper seeks its insertion. To investigate how healthy adults respond to the phenomenon resilience if constructs called protective factors and risk factors may be related to resilience and, if so, how these individuals will respond to these factors. This study was based on theories of resilience and adversity in the fields of Psychology, Administration and Sociology. With the analysis of reports and in light of the findings in the area, aimed to discuss the possible relationship between resilience and protective factors in work in healthy both physically and socially. It rises critical to the study and possible contributions of the findings to management. Finally, envision the possibility of this study was to unfold in the organizational settings, seeking to extend this study to worsen in other fields of organization with a focus on resilience and positive psychology through a subjective analysis.